MySSP: Non-stationary evolutionary sequence simulation, including indels - Michael S. Rosenberg (Evolutionary Bioinformatics, 2005)
MySSP is a new program for the simulation of DNA sequence evolution across a phylogenetic tree. Although many programs are available for sequence simulation, MySSP is unique in its inclusion of indels, flexibility in allowing for non-stationary patterns, and output of ancestral sequences. Some of these features can individually be found in existing programs, but have not all have been previously available in a single package.